Magnetic resonance imaging of breast lesions - A pathologic correlation - Gary M.K. Tse (2018)
Magnetic resonance imaging of the breast is useful in assessing breast lesions. An understanding of the pathologic characteristics of the tumors may help to understand these magnetic resonance imaging observations. Large lesional size (>10 mm), ill-defined margin, and irregular outlines are associated with malignancy. These correlate with the pathological features of breast tumor, characterized by rapid growth rate, large size, and infiltrative growth pattern, invasion into stroma resulting in desmoplasia, and hence irregular outline and margin. The detection and estimation of tumor extent of invasive lobular carcinoma is problematic, even with magnetic resonance imaging, which is considered the most sensitivity. This inaccuracy likely derives from the characteristic linear, single cells infiltration growth pattern of the tumor, which is also often underestimated by clinical examination. Estimation of tumor extent after neoadjuvant chemotherapy is also essential but problematic by imaging, as the shrunken tumor becomes fibrotic, with stromal hyalinization, diminished microvasculature and tumor break up causing size underestimation. Non-enhancement of breast tumors occurs in about 8% of cases correlates with diffuse growth pattern, particularly of infiltrative lobular carcinoma. The observation of disproportionately high non-enhancing ductal carcinoma in situ remains an enigma. Finally, early rim enhancement correlates with small cancer nests, low ratio of peripheral to central fibrosis and high ratio of peripheral to central microvessel density. These may be related to increased vascular endothelial growth factor mediated increased microvessel density as well as increased permeability, which manifest as increased rapid contrast uptake and dissipation. © 2006 Springer Science+Business Media B.V.